Cell therapy in kidney diseases: advancing treatments for renal regeneration - Salybekov, Amankeldi A.; Kinzhebay, Aiman; Kobayashi, Shuzo (Frontiers in Cell and Developmental Biology, 2024)
Kidney diseases, including acute kidney injury (AKI) and chronic kidney disease (CKD), pose a significant global health challenge, with high morbidity and mortality rates driven by rising prevalence of risk factors such as diabetes and hypertension. Current therapeutic strategies are often limited, prompting the exploration of advanced cell therapies as potential solutions. This review provides a comprehensive overview of the state of cell therapies in kidney disease, tracing the progression from preclinical studies to clinical applications. Recent studies highlited that cell-based interventions offer kidney-protective properties through mechanisms such as paracrine signaling, immune modulation, and direct tissue integration, demonstrating potential in both AKI and CKD settings. Despite promising results, challenges remain in optimizing cell therapy protocols, including cell sourcing, delivery methods, and long-term outcomes. Finally, the review addresses on efforts to enhance cell function, optimize dosing, and refine delivery techniques to improve clinical outcomes in kidney disease management.